TO THE PROBLEMS OF ECONOMIC EDUCATION IN THE REPUBLIC OF POLAND AT THE BEGINNING OF THE XXI CENTURY - Binytska, Kateryna (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the examination of theoretical approaches to the problem of economic education development in the Republic of Poland from 1989 to our days, and namely: through the content of economic education and the form of its teaching in educational establishments. On the basis of the analysis of theoretic literature, the terms economic education, economic socialization have been determined. The author reveals theoretic approaches to the mentioned problem, interprets the views of other researchers. The facts of economic education development in the country have been offered. Analysis of the role of economic education in the educational system of the Republic of Poland has been done. The tendencies of development of economic education in the country have been formulated.